PENGARUH REWARD DAN EFEKTIVITAS PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT BPR SEJAHTERA BATAM - Aprianto, Aprianto; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2021)
The business world is currently growing very rapidly because of the impact between businesses that are very competitive in showing the existence of a company or other business institution. Various methods are carried out in achieving the vision and mission of a company, one of the most important of course is human resources . The purpose of this research is to find out the effect of reward and effectiveness of training on employee performance at PT BPR Sejahtera Batam. Sampling techniques in this study is a sampling technique saturated with the number of population is all employees of PT BPR Sejahtera Batam, namely as many as 106 respondents. The data was obtained through the dissemination of questionnaires online throughout the respondents. Data quality test in this study using reliability and validity test, classical assumptions on this study using normality test, multicolinearity and heteroskedastiity and determination coefficient analysis (R2). While the hypothesis test in this study uses t test and F test using SPSS program software version 25. The results showed that the reward and effectiveness of training had a partial and simultaneous positive and significant effect on the performance of employees at PT BPR Sejahtera Batam.